The RAG1 Homeodomain Recruits HMG1 and HMG2 To Facilitate Recombination Signal Sequence Binding and To Enhance the Intrinsic DNA-Bending Activity of RAG1-RAG2 - Aidinis, Vassilis (American Society for Microbiology, 1999)
V(D)J recombination is initiated by the specific binding of the RAG1-RAG2 (RAG1/2) complex to the heptamer-nonamer recombination signal sequences (RSS). Several steps of the V(D)J recombination reaction can be reconstituted in vitro with only RAG1/2 plus the high-mobility-group protein HMG1 or HMG2. Here we show that the RAG1 homeodomain directly interacts with both HMG boxes of HMG1 and HMG2 (HMG1,2). This interaction facilitates the binding of RAG1/2 to the RSS, mainly by promoting high-affinity binding to the nonamer motif. Using circular-permutation assays, we found that the RAG1/2 complex bends the RSS DNA between the heptamer and nonamer motifs. HMG1,2 significantly enhance the binding and bending of the 23RSS but are not essential for the formation of a bent DNA intermediate on the 12RSS. A transient increase of HMG1,2 concentration in transfected cells increases the production of the final V(D)J recombinants in vivo.